As vogais médias em posição pretônica nos nomes no dialeto de Belo Horizonte: estudo da variação à luz da Teoria da Otimalidade - Marlucia Maria Alves (2008)
The objective of this research is to analyze the variation of mid-height vowels in pre-stressed-syllable position in nouns spoken in the dialect of Belo Horizonte, taking into consideration linguistic factors and phonological processes, such as vowel harmony and vowel reduction, which interfere with this production. Variation is also studied using Optimality Theory (PRINCE; SMOLENSKY, 1993; MCCARTHY; PRINCE, 1993), a model of analysis whose main objectives are to establish the universal properties of language and to characterize the possible constraints on linguistic variation. In pre-stressed position, the mid-high vowel occurs closed in most cases, with the open mid-high and high vowel occurring in more specific cases. Lowering is more likely with an open mid-high vowel or low vowel in the stressed syllable or the immediately following syllable. Raising is most likely in word-initial position with a syllabic-coda of /S/ or when forming nasalized syllables without being subject to variation. The high vowel in the stressed syllable or in the immediately following syllable also favors raising. Raising is also favored by a preceding nasal labial consonant, for front vowels, and by preceding labial and velar consonants for back vowels. Three distinct corpora were considered (POBH; ALVES, 1999; spontaneous speech). The results obtained reveal that formality at the moment of recording the data is fundamental for the occurrence of intraindividual variation. As shown in the data extracted from spontaneous speech, variation is interindividual, since each speaker opts for a manifestation of the mid-high vowel in a distinct way from others. Variation in this dialect occurs in two ways: a) variation between the mid-high closed vowel and the mid-high open vowel and b) variation between the mid-high closed vowel and the high vowel. For this variation study, using Optimality Theory, two fundamental aspects are considered: the notion of strict domination and the specification of the vowel inventory in the input. Two alternatives of variation analysis are investigated: a) rank-ordering model of EVAL, which ranks the candidates for variation and non-variable forms in a single hierarchy; and b) partial constraint ranking, establishing several hierarchies, each one selecting the best candidate in terms of variation. Moreover, characterization by means of phonological features of mid-high vowels is also considered. The features [high] and [ATR] act in concert to distinguish the mid-high and high vocalic segments in Brazilian Portuguese. Only the feature [open] is capable of determining the distinction. The analyzed results show that an approach combining classification of vocalic segments via the [open] feature with partial constraint ranking is the best method of explaining the variation in the dialect studied because speakers employ partial rankings in idiosyncratic ways particular to each case in which the mid-high vowel appears. The grammar remains, but there is a competition as to the partial ranking selected for production, mainly between the mid-high vowel and the high vowel, which were the most specific cases observed in this dialect. The feature [open] contributes to the information simplification and constraint economy.